Penerapan Model Project Based Learning (PjBL) Bermuatan Nilai dalam Materi Sistem Ekskresi Manusia untuk Meningkatkan Hasil Belajar Siswa SMA - Desriyani, Esri; Yudianto, Suroso Adi; Supriatno, Bambang (Assimilation: Indonesian Journal of Biology Education, 2018)
The aim of this research was to obtain the implementation of value-based Project Based Learning (PjBL) model toward high students learning outcomes. This research was implemented at high students with 35 people that took the purposive sampling. The Research method used weak experiment with one group pretest-posttest design. The result showed that student’s ability of concepts showed well with 62,85 % students passed and gain index of 52,2 % (sufficient The level of student acceptance of science scores is included in the high category and the gain index reaches 11% (low). Students' attitude based on observation results has a value of 3.75 (very good). The results of the questionnaire processing show that all students experience problems during learning, especially when designing projects. The results of calculations with the t-test show that the Project Based Learning Value Model influences the mastery of students' concepts and attitudes. The results of calculations with Spearman correlation show that there is a positive relationship with a low category (r = 0.2) between mastery of concepts with students' attitudes towards the acceptance of science values.